Beyond the Curriculum and the Classroom - Rachel Jackson (PRISM)
This paper reports on findings from the author’s Masters of Education project in which Classics as an after-school curriculum enhancement programme was offered to Year 9 pupils (aged 13-14) in a maintained school in Salford. The programme also incorporated excursions to supplement the extracurricular lessons delivered by the researcher (a qualified English and Classics teacher) whilst working as a teacher of English at the secondary school. Qualitative and quantitative data from a questionnaire (n=14), a focus group (n=5) and observations are presented here as a case study into the perceived impact of this curriculum enhancement programme on the participants, half of whom were identified by the school as ‘disadvantaged’.